Practical insights for enhancing primary care rehabilitation services in low-resource contexts - Maria Y. Charumbira; Karina Berner; Quinette A. Louw (African Journal of Primary Health Care & Family Medicine)
Background: Rehabilitation services are crucial for addressing the growing burden of functioning problems related to chronic conditions in low and middle-income countries. These services, however, remain limited in South Africa and Zimbabwe’s primary health care (PHC) settings.